Interaction between apolipoprotein E genotypes, excessive daytime sleepiness, and cognitive function in obstructive sleep apnea patients - Balthazar, Fernanda Maurer; Moraes, Walter André dos Santos; Hunter, James Richard; Prado, Gilmar Fernandes do; Carvalho, Luciane Bizari Coin de (Arquivos de Neuro-Psiquiatria, 2022)
Background Some studies show an association between the apolipoprotein E ε4 allele (ApoEε4) and obstructive sleep apnea syndrome (OSAS), and other studies, an association between ApoEε4 and excessive daytime sleepiness (EDS), but there are no data in the literature on the interaction between EDS, cognitive function, and ApoEε4 in patients with OSA.Objective To examine the cognitive function of adults with and without EDS and with and without ApoEε4.Methods A total of 21 male and female patients aged between 33 and 79 years, underwent a clinical interview, ApoE genotyping, neuropsychological evaluation, polysomnography, and the application of the Epworth Sleepiness Scale.Results Excessive daytime sleepiness was associated with lower intelligence quotient (IQ; total performance) and worse immediate visual memory, regardless of the ApoE genotype. Patients carrying the ApoEε3/ε4 genotype had a worse performance in divided attention, constructional praxis, perceptual organization, and cognitive flexibility. A combination of the ε4 allele and EDS potentiates the negative effect on cognition, except for immediate visual memory. In this case, patients had a worse performance in terms of processing speed, selective attention, and visuomotor coordination.Conclusions Excessive daytime sleepiness and the ApoEε3/ε4 genotype are associated with worse cognitive performance in OSA patients. The combination of EDS and ε4 allele potentiates cognitive impairment.
Keywords: Apolipoproteins E; Sleep Apnea, Obstructive; Disorders of Excessive Somnolence; Cognitive Dysfunction